Failure Analysis of 316L Stainless Steel Tubing of the High Pressure Still Condenser - T. M. Ahmed (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
Sherritt International Corporation experienced corrosion failures with the 316L stainless steel tubing in a high-pressure still condenser employed for ammonia recovery. A detailed failure analysis was conducted on the condenser tubing to determine the mode and the root cause of the failure. The analysis included both optical and scanning electron microscopy (SEM) of the inner and outer surfaces of the tube as well as characterization of the corrosion products using energy-dispersive X-ray spectroscopy (EDX). Results revealed that the corrosion attack was confined to the first ?100 mm of the tubing at the inlet where the tube was connected to the top tubesheet. The tube suffered both external stress-corrosion cracking (SCC) and crevice corrosion from the shell side (water side), and wall thinning of the inner surface (the tube side) due to erosion corrosion. It was evident that failure of one of the tubes occurred due to SCC that penetrated the whole wall thickness and resulted in a leak failure. Some prevention measures are proposed to avoid this type of corrosion attack in the future.